Common Service Center: A Tool for Empowerment of Rural Farming Community in India - V. Madhnvn Rao; R.R. Hamon; Rajashree Padhi; P. Anuradha (Journal of Agricultural Extension Management, 2025)
The post liberalisation phase brought reforms in the agriculture sector and various factors impacting high growth. Including emphasis on quality research, increased use of information Technology and expansion of agriculture extension education. Consequently, technology penetration has not only widened the scope of agriculture, but brought government’s attention to higher production vis-a- vis empowerment of rural farmers while providing agricultural information at their door step. Effective systems have been developed followed by major interventions like Green Revolution of the late 1960’s and information and Communication Technology (ICT) in the late J990’s. /CTs are not only perceived as a tool for high-end research and development but rather the new technologies and initiatives which have made significance improvements in the life-styles and the efficiency-levels of the farming community. To understand the impact of ICTs on the farming community, the role of Common Service Center (CSC) is discussed in the present article as one of the major means of dissemination of information to rural farmers.